Evidence to support phytosanitary policies–the minimum effective heat treatment parameters for pathogens associated with forest products - Noseworthy, Meghan K.; Allen, Eric A.; Dale, Angela L.; Leal, Isabel; John, Esme P.; Souque, Tyranna J.; Tanney, Joey B.; Uzunovic, Adnan (Frontiers in Forests and Global Change, 2024)
Research on reducing the movement of pests on wood products has led to several options for safer trade including heat treatment of wood to mitigate pests. In this study, pathogenic organisms commonly regulated in the trade of forest products were tested to determine the minimum heat dose (temperature and time) required to cause mortality. The mycelial stage of tree pathogens, Heterobasidion occidentale, Grosmannia clavigera, Bretziella fagacearum, Phytophthora cinnamomi, P. lateralis, P. ramorum and P. xmultiformis, which may be found in untreated wood products, were tested in vitro using the Humble water bath with parameters simulating the rate of heat applied to wood in a commercial kiln. RNA detection using reverse transcription real-time PCR was used to validate pathogen mortality following treatment for: P. ramorum, P. lateralis, P. cinnamomi, P. xmultiformis and G. clavigera. The lethal temperature for all pathogens ranged from 44 to 50°C for a 30-min treatment duration. Using this method to evaluate heat treatment for other forest product pests is recommended to accurately identify the minimum dose required to support phytosanitary trade. With more data potentially lower heat treatment applications may be recommended under specific conditions to produce more efficient and economical heat treatment schedules and reduce environmental impacts.